Circadian Regulation of Lipid Peroxidation in the Brain: Linking Ferroptosis to Neurodegenerative Vulnerability - Suraj Sen; Anit Jha; Rajeev Ratan; Neeraj Yadav; Ayush Bhardwaj (International Journal of Brain Sciences, 2026)
The human brain operates through highly coordinated physiological and biochemical processes that regulate cognition, behavior, and neural adaptability. Central to these processes are mechanisms governing brain function, neurophysiology, and neuroplasticity, which are increasingly recognized to be influenced by circadian rhythms. Recent advances in cognitive neuroscience, neuroimaging, and behavioral neuroscience have revealed that disruptions in circadian regulation can significantly impact oxidative balance within the brain, particularly through enhanced lipid peroxidation. Lipid peroxidation, a process involving oxidative degradation of membrane lipids, plays a crucial role in neuronal dysfunction and is closely associated with ferroptosis, an iron-dependent form of regulated cell death. The integration of neuropharmacology and drug development strategies has highlighted ferroptosis as a key therapeutic target in neurodegenerative conditions. Moreover, clinical neuropsychology studies indicate that oxidative damage and circadian misalignment contribute to cognitive decline and behavioral impairments. Neuroimaging and neurophysiological assessments further demonstrate that circadian disruption affects neuronal signaling, synaptic plasticity, and brain metabolism. Developmental neuroscience also suggests that early-life circadian disturbances may predispose individuals to long-term neurological vulnerabilities. The role of neuroplasticity in adapting to oxidative stress underscores the importance of maintaining circadian integrity for optimal brain health. This review explores the intersection of circadian rhythms, lipid peroxidation, and ferroptosis within the broader framework of neuroscience disciplines. It emphasizes how integrating concepts from cognitive, behavioral, and clinical neuroscience with pharmacological innovations can provide novel insights into neurodegenerative disease mechanisms. Additionally, it highlights emerging therapeutic approaches, including chronopharmacology and targeted antioxidant strategies, aimed at preserving neuronal function and improving clinical outcomes.
Keywords: Behavioral Neuroscience; Brain function; Clinical Neuropsychology; Cognitive Neuroscience; Developmental Neuroscience; Ferroptosis; Lipid peroxidation; Neuropharmacology; Neurophysiology; Neuropsychology; Oxidative stress; circadian rhythm; drug development; neuroimaging; neuroplasticity